2018
DOI: 10.13064/ksss.2018.10.3.049
|View full text |Cite
|
Sign up to set email alerts
|

Voice hygiene habits and the characteristics of Korean Voice-Related Quality of Life (K-VRQOL) among classical singers

Abstract: The purpose of this study was to investigate vocal hygiene habits and Korean Voice-Related Quality of Life (K-VRQOL) among classical singers. A total of 128 classical singers filled an online voice and K-VRQOL questionnaire, and the results were analyzed. In order to investigate the characteristics of K-VRQOL according to age groups, and the presence or absence of a history of voice problems, we conducted a two-way ANOVA. The results are as follows. Of the 128 classical singers, 28 (21.9%) with a history of vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
1
0
2
Order By: Relevance
“…They found that neither the baseline model nor the proposed model significantly degraded. Kang et al (2018) [20] studied the association between voice hygiene habits and the Korean (K-VRQOL) Voice-Related Quality of Life among classical singers. For this research, they chose 128 male 35 (27.3%) and female 93 (72.7%)) singers in South Korea who completed a questionnaire on their hygienic voice habits and the K-VRQOL scale, which evaluates the effect of voice problems on an individual's life quality.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They found that neither the baseline model nor the proposed model significantly degraded. Kang et al (2018) [20] studied the association between voice hygiene habits and the Korean (K-VRQOL) Voice-Related Quality of Life among classical singers. For this research, they chose 128 male 35 (27.3%) and female 93 (72.7%)) singers in South Korea who completed a questionnaire on their hygienic voice habits and the K-VRQOL scale, which evaluates the effect of voice problems on an individual's life quality.…”
Section: Literature Reviewmentioning
confidence: 99%
“…음성은 한 사람의 성별, 연령, 건강상태, 감정 등을 나타내며 음성에 문제가 생기면 삶의 질에 부정적인 영향을 미친다(Yoo, Kang & Kim, 2018). 노화로 인한 노년기의 음성기능 약화는 의 사소통의 불편으로 연결되며(Verdonck-de Leeuw & Mahiue, 2004;Yim et al, 2013), 인간이 대부분 목소리를 사용하여 의사 소통한다는 것을 고려하면 노년기 목소리 변화는 그들의 삶의 질(quality of life, QOL) 저하의 주요 요인이 된다 (Etter et al, 2019).…”
Section: 서론 노인성 음성이란 노화로 인해 전반적인 신체기능이 저하되unclassified
“…, 인터뷰를 통한 성악가의 음성 연구 (Pyo, https://doi.org/10.12963/csd.20774 https://www.e-csd.org 233 성악가의 음성 관리 및 음성 지식에 대한 질적연구 • 박상희 외 2011a, 2011b), 설문지를 통한 성악가의 음성 연구 (Braun-Janzen & Zeine, 2008;Jun et al, 2018;Kang, Kim, & Yoo, 2018;Weekly et al, 2018), 문헌 연구를 통한 성악가의 음성 연구 (Kim & Yoo, 2017;Shin, 2004) (Awan, 1991;Choi, Nam, Kim, Kim, & Choi, 2006;Chung, 1998Chung, , 1999Howard, Lindsey, & Allen, 1990;Ship, 1987)…”
unclassified